Pathology of Peripheral Neuroblastic Tumors - Hiroyuki Shimada; Hideki Sano; Florette K. Hazard (The Korean Society of Pediatric Hematology-Oncology, 2020)
Peripheral neuroblastic tumors (pNTs including Neuroblastoma, Ganglioneuroblastoma and Ganglioneuroma) are biologically and clinically heterogeneous. In order to develop efficient clinical treatment protocols of this disease, patients are stratified into different risk groups based on the combination of so-called prognostic factors. In this review, the prognostic factors are classified as clinically defined (Clinical staging and Age at diagnosis), histopathologically defined [International Neuroblastoma Pathology Classification (INPC) distinguishing Favorable Histology (FH) Group and Unfavorable Histology (UH) Group] and genetically/molecularly defined [MYCN oncogene amplification, DNA index, Segmental chromosomal aberrations, ALK (Anaplastic Lymphoma Kinase) mutation/amplification and Abnormal maintenance/elongation of telomeres], are outlined. According to the Children's Oncology Group (COG) Neuroblastoma studies, the survival rate of patients in low- or intermediate-risk group is more than 90%. In contrast, the survival rate of patients in the high-risk group remains less than 50% despite currently available high-intensity and multimodal therapy. As described in the genetically/molecularly defined prognostic factors, tumors in the high-risk group, majority of which are classified into the UH group according to the INPC, are molecularly heterogeneous. Based on the recent progress of precision medicine along with our correlative analyses between molecular alterations and their morphological manifestations, four subgroups; i.e., MYC subgroup, TERT subgroup, ALT subgroup and Null subgroup, are identified immunohistochemically in the UH group for future management of the patients with this unique d isease.